KHIYAR KHIYAR AIB TERHADAP PRAKTIK JUAL BELI ONLINE MOTOR ANTIK - Fetri Fatorina; Masdar Masdar; Chamid Sutikno (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
Buying and selling online has two sides of view, namely the positive and negative sides. This is due to the difference in buying and selling mechanisms between buying and selling online and buying and selling directly. On the positive side, both parties, namely sellers and buyers, both benefit in terms of ease and speed of access to see the object of sale and purchase, in this case the CB 100 type antique motorbike. On the negative side, buyers tend to be disappointed if the goods purchased do not match those on the promotion. In fact, it is often found that there are defects in the goods purchased. It can be assumed that in the practice of buying and selling online, khiyar rights are not implemented. The problem raised in this research is what is the position of khiyar disgrace in online buying and selling of CB 100 type antique motorbikes? The subjects of this study were the sellers and buyers of the CB 100 community in the Purwokerto area. The object of this research is the online buying and selling transaction of CB 100 type antique motorbikes. The methods used are observation, interviews, documentation. The results of this study state that the position of khiyar disgrace in online buying and selling of antique motorbikes has been fulfilled. But to determine whether to buy or not they use khiyar ru'yah. So that it can be said that online buying and selling of antique CB 100 type motorbikes is a practice that is prohibited by Islam. This practice contains more harm than benefit. Even though according to Islamic law, the buying and selling contract is valid. However, the practices and systems used are contrary to religious rules and prohibited by syara'